From Skinned Cats to Angels in Fur: Feline Traces and the Start of the Cat-Human Relationship in Victorian England - Hilda Kean (Cahiers Victoriens et Edouardiens)
This article focuses on the changing status of cats from various backgrounds during the nineteenth century in Britain. Although the introduction of initial animal welfare legislation improved the relative condition of some forms of cattle and horses, cats continued in the early decades to be skinned and tortured. By analysing both court and newspaper reports, as well as parliamentary procedures, the lives of a range of cats were being started to be changed later in the nineteenth century. Further, the impact of eating different types of food over time also influenced cats. The issuing of manuals on cat welfare, as well as analysis of cats’ employment in different institutions, led to additional perspectives on cats. By the late nineteenth century cats started to be regarded in far more positive ways than those who were treated badly many years before.